Comparative study of e-cigarette aerosol and cigarette smoke effect on ex vivo embryonic chick lung explants - Silva-Ribeiro, Tiago (2023)
Electronic cigarette usage has significantly expanded among young people and pregnant women in the last decade. Although there are already some data regarding the short- and long-term consequences of e-cigarettes on human health, their effect on embryo and lung development still needs to be fully disclosed. In this sense, this study describes, for the first time, the impact of electronic cigarette aerosol on early lung development. For this purpose, ex vivo chick (Gallus gallus) embryonic lungs were cultured in vitro for 48h in e-cigarette aerosol exposed-medium or unexposed medium. Chick lung explants were also cultured in a cigarette smoke-exposed medium for comparison purposes. Lung explants were morphologically analyzed to assess the impact on lung growth. Additionally, TNF- levels were determined in the supernatant as a marker of pro-inflammatory response. The results suggest that electronic cigarette aerosol impairs lung growth and promotes lung inflammation. However, its impact on early lung growth seems less detrimental than conventional cigarette smoke. This work provides significant data regarding the impact of e-cig aerosol, adding to the efforts to fully understand its effect on embryo development. The validation of these effects may eventually lead to new tobacco control recommendations for pregnant women.